2007
DOI: 10.1021/ie0705150
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Effects of Nanocrystalline Lithium Zirconate on Its CO2 Capture Properties

Abstract: A soft-chemistry route has been used for preparation of pure and promoted nanocrystalline lithium zirconate with different stoichiometries. The objective of this investigation has been to study the effect of different compositions on the acceptor and optimize the working properties of lithium zirconate. Special attention has been given to study the effect of different Li 2 O-ZrO 2 stoichiometries on the CO 2 capture rates. In addition, the partial substitution of Li 2 O with K 2 O as a promoter has been addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 27 publications
2
68
0
Order By: Relevance
“…27 Fernandez and co-workers showed that doping LiZrO 3 with K 2 CO 3 enhanced CO 2 absorption rates. 28 It was claimed that loading of potassium favors the diffusion of CO 2 through the LiCO 3 layer that is formed in the surface of the acceptor during the capture reaction. Our explanation for the increase in CO 2 capacity is based on the geometric rearrangement and defect surface structure of the various K-loaded HTs and is discussed below.…”
Section: Resultsmentioning
confidence: 99%
“…27 Fernandez and co-workers showed that doping LiZrO 3 with K 2 CO 3 enhanced CO 2 absorption rates. 28 It was claimed that loading of potassium favors the diffusion of CO 2 through the LiCO 3 layer that is formed in the surface of the acceptor during the capture reaction. Our explanation for the increase in CO 2 capacity is based on the geometric rearrangement and defect surface structure of the various K-loaded HTs and is discussed below.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of K-Li 2 ZrO 3 , the formation of a eutectic molten carbonate layer of Li 2 CO 3 and K 2 CO 3 enhances the adsorption kinetic rate by increasing the CO 2 diffusion rate through the external layer. However, Ochoa-Fernandez et al [138] showed that despite the positive effect of potassium carbonate doping into Li 2 ZrO 3 on the kinetic rate of CO 2 adsorption, the CO 2 capture capacity and cyclic stability of sorbent was lowered by the addition of potassium. Figure 5.…”
Section: Ceramic Co 2 Sorbentsmentioning
confidence: 99%
“…42−44 We anticipated that the rare-earth ceramic particles will act as a virtual shell against the segregation of absorbent phase, thereby impeding particle agglomeration and imparting absorbent powders with superior performance. 28) and fumed silica in the molar ratio 2.2:1. The powders were initially mixed with a pestle and mortar and then ball-milled for 24 h in isopropanol.…”
Section: Introductionmentioning
confidence: 99%